2020
DOI: 10.1111/and.13612
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of anatomical endoscopic enucleation of the prostate: A systemic review and meta‐analysis

Abstract: Benign prostatic hyperplasia (BPH) is the most common aetiology of bladder outlet obstruction and lower urinary tract symptoms (LUTS) in men. While medical treatment is considered as the first-line treatment for male LUTS secondary to BPH, a substantial portion of men would require surgical intervention because of insufficient relief of LUTS with medications or having any absolute indication for surgery, such as recurrent or refractory urinary retention, recurrent urinary tract infections, bladder stones or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…A meta-analysis published by Chen et al (2020) concluded that ThuLEP is a superior procedure to TURP and HoLEP. 14 A few other investigators have also concluded that ThuLEP is a superior enucleation technique to HoLEP. 8 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published by Chen et al (2020) concluded that ThuLEP is a superior procedure to TURP and HoLEP. 14 A few other investigators have also concluded that ThuLEP is a superior enucleation technique to HoLEP. 8 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…AEEP resulted in greater prostate tissue removal, reduced hemoglobin loss, shorter catheterization time, and shorter LOS. 63 Recent evidence supports the use of AEEP in patients with BPH on anticoagulant (AC) or antiplatelet (AP) therapy. [64][65][66] AEEP has demonstrated durable results with a low reoperation rate of 0-3.7% (attributed to adenoma regrowth) on long-term follow-up of up to 18 years.…”
Section: Anatomic Endoscopic Enucleation Of the Prostate (Aeep)mentioning
confidence: 99%
“…Está técnica ha demostrado menor tasa de sangrado, transfusión, tiempo con catéter y estadía hospitalaria que la cirugía abierta, pero con mayor tiempo operatorio 3 . De manera similar, al compararla con la resección transuretral de próstata ha demostrado mejores resultados funcionales, mayor volumen de tejido resecado, menor sangrado, menor tasa de transfusión y menor tiempo de hospitalización, pero con mayor tiempo operatorio 4 .…”
Section: Introductionunclassified